Green synthesized silver nanoparticles with mushroom extracts of Paxina leucomelas and Rhizopogon luteolus induce ROS-Induced intrinsic apoptotic pathway in cancer cells - Gökşen Tosun, Nazan; Kaplan, Özlem; Imamoğlu, Rizvan; Türkekul, İbrahim; Gökçe, İsa; Özgür, Aykut (Taylor and Francis Ltd., 2024)
The green synthesized silver nanoparticles (AgNPs) provide many advantages including the production of nanoparticles without using toxic compounds and solvents, the low-cost of the synthesis process, the existence of a large number of biological substances as a reducing agent of silver, and the production of nanoparticles in desired parameters. In this study, the PL-AgNPs and RL-AgNPs were synthesized by microwave-assisted green synthesis method using extracts of Paxina leucomelas and Rhizopon luteolus. The synthesized P. leucomelas-AgNPs (PL-AgNPs) and R. luteolus-AgNPs (RL-AgNPs) were characterized by UV–Vis, FTIR, XRD, DLS, S-TEM, and EDS analysis. Anticancer activity of the synthesized AgNPs was investigated on human cancer cells lines. Obtained results demonstrated that the PL-AgNPs and RL-AgNPs decreased cancer cell viability via ROS-mediated intrinsic apoptotic pathways. These findings strongly suggest that the AgNPs formed by aqueous extracts of P. leucomelas and R. luteolus may be introduced as an alternative apoptosis inducer in cancer drug discovery. © 2022 Taylor & Francis Group, LLC.
Keywords: apoptosis; cancer; green synthesis; mushrooms; Silver nanoparticles